Simplifying

-4 + -1(x + y) = 0

-4 + (x * -1 + y * -1) = 0

-4 + (-1x + -1y) = 0

Solving

-4 + -1x + -1y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.

-4 + -1x + 4 + -1y = 0 + 4

Reorder the terms:

-4 + 4 + -1x + -1y = 0 + 4

Combine like terms: -4 + 4 = 0

0 + -1x + -1y = 0 + 4

-1x + -1y = 0 + 4

Combine like terms: 0 + 4 = 4

-1x + -1y = 4

Add 'y' to each side of the equation.

-1x + -1y + y = 4 + y

Combine like terms: -1y + y = 0

-1x + 0 = 4 + y

-1x = 4 + y

Divide each side by '-1'.

x = -4 + -1y

Simplifying

x = -4 + -1y

-4-(x+y)=0

-4(-x+y)=0

4x-4y=0

-4y=4x

y=-1x

OR

y=-x

Hope this helps!

- Anybody got the answers to Dental Law, Charting And Cavity Classification 02400300?
- An e-mail should:?
- Where can I find info about classes and tutorials for elementary home school students?
- What is the point in a homeschool group?
- What is the best AP Physics B geared text book that will help me learn physics?
- Do you think homework is necessary for kids at school?
- English A level equivalent?
- Does anyone homeschool that isn't super religious?
- Some questions on homeschooling in West Virginia...?
- Is home schooling a 17 year old son permitted in Saudi Arabia?